10,000 years of mandibular evolution in southern South America: Implications for morphological diversification - Menendez, Lumila Paula (2019)
South America (SA) was the last continent to be colonized by modern humans. One of the relevant research questions that still remain to be addressed is how SA populations became differentiated. Previous studies that pointed to tackle this question analyzed molecular, cranial, dental, and postcranial variation. However, there are no studies so far analyzing mandibular variation with a wide temporal-spatial coverage in SA, what might be biasing current interpretations. Mandibular variation in modern humans has been described by a reduction pattern across time, which was interpreted either as a result of evolutionary history and/or the differential impact of diverse subsistence strategies. The aim of this study is to evaluate morphometric changes in southern SA mandibles for discussing which evolutionary processes were involved during human diversification. For this, a total of 28 3D landmarks were registered in a sample that includes 6 early-middle Holocene specimens (EMH) from the Argentinean Pampas and 10 late Holocene populations (LH) from SA (N~200). Results of the PCA and CVA showed that the EMH specimens are primarily differentiated from the LH ones, and secondarily associated to the southern samples. Shape and size variation shows that more robust mandibles with a largerbody and ramus characterize EMH. Additionally, the spatial regressions performed show that diet contributes to explain 40% of mandible shape variation. Overall, such patterns could be interpreted either as the result of population diversification driven by selection and/or genetic drift. A discussion considering previous studies in the area and alternative explanations will be presented.